In vivo monitoring of rat macrophages labeled with poly(l-lysine)-iron oxide nanoparticles - Babič, Michal; Schmiedtová, Martina; Poledne, Rudolf; Herynek, Vít; Horák, Daniel (Journal of biomedical materials research. Part B, Applied biomaterials, 2015)
Coprecipitation of FeCl2 and FeCl3 with aqueous ammonia was used to prepare iron oxide nanoparticles dispersible in aqueous medium. Oxidation of the particles with sodium hypochlorite then yielded maghemite (γ-Fe2 O3 ) nanoparticles which were coated with two types of coating -d-mannose or poly(l-lysine) (PLL) as confirmed by FTIR analysis. The particles were <10 nm according to transmission electron microscopy. Their hydrodynamic particle size was ∼180 nm (by dynamic light scattering). The d-mannose-, PLL-coated, and neat γ-Fe2 O3 particles as well as commercial Resovist® were used to label rat macrophages. The viability and contrast properties of labeled macrophages were compared. PLL-coated γ-Fe2 O3 nanoparticles were found optimal. The labeled macrophages were injected to rats monitored in vivo by magnetic resonance imaging up to 48 h. Transport of macrophages labeled with PLL-γ-Fe2 O3 nanoparticles in rats was confirmed. Tracking of macrophages using the developed particles can be used for monitoring of inflammations and cell migration in cell therapy.
Keywords: Animals; Magnetic Resonance Imaging; velikost částic; makrofágy; Particle Size; Nanoparticles; železité sloučeniny; Macrophages; magnetická rezonanční tomografie; nanočástice; Cell Tracking; polylysin; buněčný tracking; Male; kontrastní látky; krysa rodu Rattus; Polylysine; zvířata; mužské pohlaví; Contrast Media; Rats; Ferric Compounds